Comparison of optical and chemical properties of thermally evaporated and spin-coated chalcogenide As-S thin films targeting electron beam lithography applications - Pálka, Karel; Jančálek, Jiří; Šlang, Stanislav; Grinco, Marina; Vlček, Miroslav (Elsevier Science BV, 2019)
Presented work compares optical and chemical properties of As30S70, As35S65 and As40S60 amorphous chalcogenide thin films deposited by thermal evaporation and by spin-coating. Structural and compositional differences given by the chosen deposition technique and post deposition treatment were revealed by Raman spectroscopy and EDS. Applicability of studied thin films in electron beam lithography was investigated using both monoamine and diamine based developers. Thermally evaporated thin films exhibited negative etching contrary to the spin-coated films which showed positive etching. Studied thin films proved to be suitable positive and negative photoresists for both grey-scale and step-like lithography.
Srovnání optických a chemických vlastností napařených a spin-coatingem deponovaných tenkých vrstev As-S s cílením na aplikace elektronové litografie
Keywords: dissolution; glasses; thickness; rozpouštění; skla; tloušťka